A Lateralized Deficit in Morphine Antinociception after Unilateral Inactivation of the Central Amygdala - Manning, Barton H. (J Neurosci, 1998)
The amygdala is a forebrain region that is receiving increasing attention as a modulator of pain sensation. The amygdala contributes to antinociception elicited by both psychological factors (e.g., fear) and exogenous opioid agonists. Unlike the midbrain periaqueductal gray matter (PAG) or rostral ventromedial medulla, the amygdala is a pain-modulating region that has clear bilateral representation in the brain, making it possible to determine whether pain-modulating effects of this region are lateralized with respect to the peripheral origin of noxious stimulation. Unilateral inactivation of the central nucleus of the amygdala (Ce) plus adjacent portions of the basolateral amygdaloid complex (with either the excitotoxin NMDA or the GABA(A) agonist muscimol) reduced the ability of morphine to suppress prolonged, formalin-induced pain derived from the hindpaw ipsilateral, but not contralateral, to the inactivated region. This effect was evident regardless of the nociceptive scoring method used (weighted scores or flinch-frequency method) and wasnot accompanied by a concurrent reduction in morphine-induced hyperlocomotion. Unilateral lesions restricted to the basolateral amygdaloid complex (i.e., not including the Ce) did not reduce the ability of morphine to suppress formalin-induced pain derived from either hindpaw. The results constitute the first report of a lateralized deficit in opioid antinociception after unilateral inactivation of a specific brain area and show the first clear neuroanatomical dissociation between antinociceptive and motor effects of systemically administered morphine in the rat. The amygdala appears to modulate nociceptive signals entering the ipsilateral spinal dorsal horn, probably through monosynaptic connections with ipsilateral portions of the PAG.